THE EFFECT OF COMPENSATION ON MEDICAL DOCTOR AND NURSE WITH WORK DISCIPLINE AS AN INTERVENING VARIABLE (CASE STUDY OF MEDICAL DOCTOR AND NURSE IN UNITED STATES PUBLIC HEALTH SERVICE) - Zhenyu Cui; John Zysman (PT. Radja Intercontinental Publishing, 2021)
The sampling technique used was the census method, where the entire population of 40 Medical Doctor and Nurses at Medical Doctor And Nurse In United States Public Health Service, was sampled in this study. Data collection techniques by conducting a review study of books, literature, records, and reports that have something to do with the problem being solved. The results of this study are stated that: From the table above, a tcount value of 5.399 is obtained with α = 5%, ttable (5%; nk = 38) obtained a ttable value of 1.685. From this description it can be seen that tcount (5.399) > ttable (1.685) , likewise with a significance value of 0.00 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the compensation variable (X) has a positive and significant effect on work discipline (Y1). tcount value of 2.939 With α = 5%, ttable (5%; nk = 38) obtained ttable value of 1.685 From this description it can be seen that tcount (2.939) > ttable (1.685), and its significance value is 0.00 <0, 05 it can be concluded that the second hypothesis is accepted, meaning that compensation (X) has a significant effect on Medical Doctor and Nurse performance (Y2). tcount value of 3.294 With α = 5%, ttable (5%; nk = 38) obtained ttable value of 1.685 From this description it can be seen that tcount (3.294) > ttable (1.685), and its significance value is 0.00 <0, 05, it can be concluded that the third hypothesis is accepted, meaning that work discipline (Y1) has a positive and significant effect on Medical Doctor and Nurse performance (Y2). In the picture above the path analysis shows the direct effect of variable X on variable Y2 of 0.403.